Cloud Computing and Information Technology Strategy - Antonio Mariano Carlos Junior (Journal of Technology Management & Innovation, 2013)
Cloud computing represents a new paradigm that enables the utility computing model in which computing resources are offered and consumed as a service on demand, pay as you go, in a model similar to that of electricity. The objective of this work is to identify threats and opportunities of the cloud computing model and its influence on the strategy of companies that consume Information Technology. To do so, a survey was conducted with leading IT executives from 64 medium and large companies in Brazil. We noticed the influence of cloud computing in migrating the focus of the corporate IT departments to the management of services and contracts, resulting into the demand for professionals with IT analyst integrated and business profiles.